(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Domestic violence is a pervasive societal challenge with significant effects for student development and academic performance. This study investigates the impact of domestic violence on the academic performance of secondary school students in Ikere-Ekiti, Ekiti State, Nigeria. The study specifically examines the prevalence and forms of domestic violence, its effects on academic outcomes, and the broader influence on students’ educational achievements, while offering actionable recommendations to address the issue. The research employs a descriptive survey design, utilizing both qualitative and quantitative methods to gather data from a representative sample of secondary school students, teachers, and community stakeholders. Structured questionnaires, interviews, and focus group discussions were the primary tools used to collect data. The sample was selected using a multi-stage sampling technique to ensure diversity and inclusivity. Statistical analyses, including descriptive and inferential statistics, were applied to interpret the findings. The study adopted behavioural theory as theoretical framework. The study reveals a high prevalence of domestic violence among secondary school students in Ikere-Ekiti, with physical, emotional, and psychological abuse being the most common forms. The findings indicate that students exposed to domestic violence often exhibit poor academic performance, including lower grades, absenteeism, and reduced classroom participation. Furthermore, the study identifies that the trauma and stress associated with domestic violence significantly impair students’ cognitive abilities, concentration, and overall motivation to learn. Based on these findings, the study recommends the implementation of comprehensive support systems for affected students, including counseling services, teacher training on identifying and addressing domestic violence cases, and fostering safe school environments. It also advocates for stronger community awareness campaigns and policy interventions by the government to curb domestic violence and its adverse effects.